2009
DOI: 10.1016/j.apmr.2008.07.028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hypertonic Dextrose Injection on Connective Tissue and Nerve Conduction Through the Rabbit Carpal Tunnel

Abstract: Objective To investigate the effects of hypertonic dextrose injection on the subsynovial connective tissue (SSCT) in a rabbit model. We hypothesized that dextrose injection would induce proliferation of the SSCT, hinder median nerve conduction, and alter SSCT mechanical properties similar to what is observed in patients with carpal tunnel syndrome (CTS). Design Randomized, controlled prospective study. Setting Not applicable. Participants New Zealand white rabbits (N=28) weighing 4.0 to 4.5kg. Interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 35 publications
9
54
2
Order By: Relevance
“…Similar observations have been made in CTS animal models (Moriya et al, 2011; Vanhees et al, 2013; Yoshii et al, 2009b). Results of this study do, however, refine the analysis, allowing for a more detailed description of how the mechanical behavior is different.…”
Section: Discussionsupporting
confidence: 85%
“…Similar observations have been made in CTS animal models (Moriya et al, 2011; Vanhees et al, 2013; Yoshii et al, 2009b). Results of this study do, however, refine the analysis, allowing for a more detailed description of how the mechanical behavior is different.…”
Section: Discussionsupporting
confidence: 85%
“…With regard to EP testing, a previous study [23] had shown that the normal rabbit median nerve motor latency was 1.74±0.25 ms and the normal motor amplitude was 1.71±0.6 mV. Based on these data, a sample size of 12 would be more than sufficient to detect a difference of 25% in either value, which we thought would be a clinically important difference.…”
Section: Resultsmentioning
confidence: 95%
“…The use of hypertonic dextrose to induce SSCT fibrosis in an animal model of CTS has been previously reported [14,23]. This model is based on the concept of proliferative therapy or prolotherapy, in which an irritant, in this case a hypertonic solution, is injected in order to initiate neovascularization and to stimulate collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations